2017
DOI: 10.1017/mor.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

State-Mediated Globalization Processes and the Adoption of Corporate Social Responsibility Reporting in China

Abstract: Despite the prevalence of global diffusion, little is known about the processes by which international practices are adopted and adapted within organizations around the world. Through our qualitative research on the introduction of corporate social responsibility (CSR) reporting at two leading Chinese companies, we identify a unique set of political mechanisms that we label state-mediated globalization, whereby powerful nation-state actors influence the ways in which corporations adopt and adapt global norms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 59 publications
1
49
0
Order By: Relevance
“…; Marquis et al. ). The findings of Hummel and Schlick () imply that sustainability reports under mandatory disclosure may show low quality to gain legitimacy while at the same time disguise the firm's true performance compared with those under voluntary disclosure.…”
Section: Hypotheses Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…; Marquis et al. ). The findings of Hummel and Schlick () imply that sustainability reports under mandatory disclosure may show low quality to gain legitimacy while at the same time disguise the firm's true performance compared with those under voluntary disclosure.…”
Section: Hypotheses Developmentmentioning
confidence: 98%
“…In particular, the state control plays an exceptional role in Chinese CSR practices. State enterprises were the first Chinese firms to publish CSR reports and today, the disclosure of CSR is a virtually mandatory requirement for firms with high levels of state ownership (Hung et al 2013;Marquis et al 2017). The findings of Hummel and Schlick (2016) imply that sustainability reports under mandatory disclosure may show low quality to gain legitimacy while at the same time disguise the firm's true performance compared with those under voluntary disclosure.…”
Section: The Moderating Role Of State Controlmentioning
confidence: 99%
“…These could include institutions such as credit agencies and standard setting bodies (Khanna & Palepu, 2010), as well as programs to develop intermediary skills, human capital and relevant expertise. Marquis, Yin and Yang (2013) for instance analyzed how the Chinese government and large companies participated in the creation of a new set of China specific CSR reporting standards and training programs to help Chinese companies implement this new global practice. More generally, London and Hart (2004) found that successful MNCs often incorporate local capacity building such as training programs and advisory services directly into their business models.…”
Section: Described How In Countries Likementioning
confidence: 99%
“…140 While the National Action Plan does not expressly include a separate section on business and human rights, some commentators 131 (Human Rights Watch 2011). 132 (Zhu 2017;Xu et al 2017;Shahab et al 2018;Qiu 2017;Marquis et al 2017;Marquis and Qian 2014;Guttman et al 2018;Aidoo et al 2017). 133 SASAC performs the following functions: 'supervises and manages the State-owned assets of centrally administered State-owned enterprises'; it is responsible for the supervision and for ensuring the increase in the value of State-owned assets; it takes charge of the reform and restructuring of State-owned enterprises; it appoints and removes the top executives of the entities supervised; it manages the day-to-day operation of the supervisory panels; takes charge of the State-owned capital operational budget and ensures that surplus capital is returned to the State; it ensures that the supervised enterprises apply relevant legislation, regulation and principles; and it takes charge of the 'fundamental management' of those entities.…”
Section: The Chinese State Ownership Policymentioning
confidence: 99%